ANALISIS PHYSICAL FITNES PEMAIN BOLAVOLI PUTRA EKSTRAKULIKULER MA TARBIYATUT THOLABAH - SUYETNO, AHMAD; SUDIJANDOKO, ANDUN (Jurnal Kesehatan Olahraga, 2019)
ABSTRACT PHYSICAL FITNES ANALYSIS OF EXTRACULICULAR MALE EXTRACULICULAR BOLAVOLY PLAYERS. TARBIYATUT THOLABAH Name : Ahmad Suyetno Registration Number : 12064084235 Study Program : S-1 Sport Science Concentration :Health and Recreation Education Faculty : Sport Science University :Universitas Negeri Surabaya Advisor : Dr.Andun Sudijandoko M.kes The purpose of holding a volleyball tournament between schools is to seek the talent of Indonesian children to make the club or team name and school name scent. As well as forming the character of the child so that it becomes a useful human resource for the nation and the state Based on the background of the problem, the objectives of this study can be described as follows to analyze the physical condition of the MA volleyball extracurricular male. Tarbiyatut Tholabah Lamongan. By the way using descriptive statistics (frequency tabulation). In this study the data that has been obtained will be analyzed by describing the results of the research obtained from the test, namely the individual age fitness test (TKJI). Most of the Bolavoli players, MA TARBIYATUT THOLABAH and the results of calculations carried out with SPSS assistance (Statistical Package for the Social Science) 21 are in the moderate category with 4 and a percentage of 33.33%, good categories with 7 people and a percentage of 58.33%, very good category as many as 1 person with a percentage of 8.33%. From the results obtained in the data collection and calculation of the results of data retrieval using SPSS 21 (Statistical Program For Solution Science for Windows Evaluation 21), the majority of the physical fitness level of MA Tarbiyatut Tholabah male volleyball players is in good category. Keywords: Individual Physical Fitness, Volleyball, Phsyic ConditionABSTRAK ANALISIS PHYSICAL FITNES PEMAIN BOLAVOLI PUTRA EKSTRAKULIKULER MA. TARBIYATUT THOLABAH Nama : Ahmad Suyetno NIM : 12060484235 Program Studi : S-1 Jurusan : Pendidikan Kesehatan dan Rekreasi Fakultas : Fakultas Ilmu Keolahragaan Nama Lembaga : Universitas Negeri Surabaya Pembimbing : Dr. Andun Sudijandoko M.kes Tujuan diselenggarakan Turnamen bolavoli antar sekolah menenegah ini adalah mencari bakat anak bangsa Indonesia untuk mengharumkan nama club atau teamnya dan nama sekolahan. Serta membentuk watak anak agar menjadi sumber daya manusia yang berguna bagi bangsa dan negara Berdasarkan latar belakang masalah, maka yang menjadi tujuan dari pada penelitian ini dapat diuraikan sebagai berikut untuk menganalisa kondisi fisik pada ekstrakulikuler bolavoli putra MA. Tarbiyatut Tholabah Lamongan. Dengan cara menggunakan statistik deskriptif (tabulasi frekuensi). Dalam penelitian ini data yang sudah diperoleh akan dianalisis dengan mendeskripsikan hasil penelitian yang diperoleh dari tes tersebut,yakni tes kebugaran jamani individu (TKJI). Sebagian besar pemain Bolavoli putra MA TARBIYATUT THOLABAH dan hasil perhitungan yang telah dilakukan dengan bantuan SPSS (Statistical Package for the Social Science) 21 berada dalam kategori sedang dengan jumlah 4 dan presentase sebesar 33,33%, kategori baik dengan jumlah 7 orang dan presentase sebesar 58,33%, kategori sangat baik sebanyak 1 orang dengan presentase sebesar 8,33% Dari hasil yang didapat dalam pengambilan data dan perhitungan hasil pengambilan data mmenggunakan bantuan SPSS 21 (Statistical Program For Solution Science for windows evaluation 21) maka sebagian besar tingkat kebugaran jasmani pemain bolavoli putra MA Tarbiyatut Tholabah dalam kategori baik. Kata kunci : Kebugaran Jasmani Individu, BolaVoli, Kondisi Fisik